The Land Use Act and the Challenges of Housing in Nigeria - Ejura Attah , Christiana (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Shelter is one of the basic needs of human beings. It is for this reason that individuals and the governments always strive to ensure its availability. The Land Use Act, which was enacted in 1978, has, as one of its objectives, to ensure that land was easily made available to both the government and individuals for housing. However, after over four decades of its implementation, the Act has become a chimera to housing. Rather than being a catalyst to urban development in Nigeria, the Land Use Act has become a stumbling block to the attainment of the dream of availability of houses for all Nigerians. The main thrust of this paper is to demonstrate that the provisions of shelter, especially in the urban areas, is still beyond the reach of an average Nigerian. Relying on the doctrinal research method, this paper examines government housing policies from the colonial period to date and concludes that the policies and the Land Use Act have not met the housing needs of Nigerians. The paper therefore calls for a re-examination of the implementation of the provisions of the Act to remove the bottlenecks that stand in the way of acquisition of land for the purpose of the construction of houses by average individuals and government, especially in the urban areas.